Penerapan Metode Static Forensics untuk Ekstraksi File Steganografi pada Bukti Digital Menggunakan Framework DFRWS - Sunardi; Imam Riadi; Muh. Hajar Akbar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Steganography is one of the anti-forensic techniques that allow criminals to hide information in other messages so that during the investigation, the investigator will experience problems and difficulty in getting evidence of original information on the crime. Therefore an investigator is required to have the ability to be able to find and extract (decoding) using the right tools when opening messages that have been inserted by steganography techniques. The purpose of this study is to analyze digital evidence using the static forensics method by applying the six stages to the Digital Forensics Research Workshop (DFRWS) framework and extracting steganography on files that have been compromised based on case scenarios involving digital crime. The tools used are FTK Imager, Autopsy, WinHex, Hiderman, and StegSpy. The results of extraction of 9 out of 10 files that were scanned by steganography files had 90% success and 10% of steganography files were not found, so it can be concluded that the extraction files in steganographic messages can be used as legal digital proofs according to law.